Self-perception of health and quality of life in patients on renal replacement therapy undergoing hemodialysis: a case-control study - Diego José Gambin; Felipe Gomes Dallepiane; Leonardo Saraiva; Marciele Cristiane Spanenberg Führ; Fabiana Piovesan; Caroline Mirek; João Paulo De Carli; Micheline Sandini Trentin (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Chronic kidney disease (CKD) presents challenges to human health and quality of life, with care primarily focusing on renal function and comorbidity management. Several studies confirm the relationship between oral and systemic conditions of patients. Therefore, CKD and periodontal disease can be related because they are both inflammatory conditions that further increase the risk of other pathologies. The impact of CKD on oral health and overall quality of life is an area of interest. OBJECTIVES: To evaluate patients with CKD undergoing renal replacement therapy regarding the levels of self-perception of oral health and quality of life. DESIGN SETTING: This case-control study was conducted jointly at the Universidade de Passo Fundo and Hospital São Vicente de Paulo, Brazil. METHODS: This study included two patient groups: 1) Case group with CKD (CGA) comprising 116 patients; 2) Control group without CKD (CGO) composed of 124 patients. We used a structured questionnaire and the Oral Health Impact Profile (OHIP-14). We used the Chi-square and Wilcoxon-Mann-Whitney tests as well as an analysis of variance measure (P < 0.05). RESULTS: The systemic diseases most prevalent among our patient cohort included hypertension (16.9% CGO and 75.9% CGA) and diabetes mellitus (8.9% CGO and 38.8% CGA). The systemic health perception was good in 66.9% of the CGO group and average in 42.2% of CGA group members. Oral health perception was good in 46% of CGO and 50% of CGA group members. Results of the self-assessment for quality of life showed a statistically significant difference between the groups for physical domain, physical disability, and social disadvantage. A comparison between the control and case (CKD) groups, based on the OHIP-14 score, showed statistically significant differences in the functionality (P < 0.006), physical disability (P < 0.042), and social disadvantage (P < 0.031) domains for the CKD group. CONCLUSION: Patients with CKD have lower rates of self-perception of oral health and quality of life than individuals without CKD.